Recent developments and prospects of sustainable remediation treatments for major contaminants in soil: A review - Lee, Hyeyeon; Sam, Kabari Simeon; Coulon, Frederic; De Gisi, Sabino; Notarnicola, Michele; Labianca, Claudia (Elsevier, 2024)
Rapid industrialisation and urbanisation are contributing to the entry of emerging contaminants into the environment, posing a significant threat to soil health and quality. Therefore, several remediation technologies have been investigated and tested at a field scale to address the issue. However, these remediation technologies face challenges related to cost-effectiveness, environmental concerns, secondary pollution due to the generation of by-products, long-term pollution leaching risks, and social acceptance. Overcoming these constraints necessitates the implementation of sustainable remediation methodologies that prioritise approaches with minimal environmental ramifications and the most substantial net social and economic advantages. Hence, this review delves into diverse contaminants that threaten soil health and quality. Moreover, it outlines the research imperatives for advancing innovative remediation techniques and effective management strategies to tackle this concern. The review discusses a remediation treatment train approach that encourages resource recovery, strengthens the circular economy, and employs a Life Cycle Assessment (LCA) framework to assess the environmental impacts of different remediation strategies. Additionally, the study explores mechanisms to integrate sustainability principles into soil remediation practices. It underscores the necessity for a comprehensive and systematic approach that takes into account the economic, social, and environmental consequences of remediation methodologies in the development of sustainable solutions.
Keywords: Clean-up; Contamination; Life cycle assessment; Resource recovery; Sustainability